Case Report: An Unusual Course of Angiosarcoma After Lung Transplantation - Bos, Saskia; Daniëls, Liesbeth; Michaux, Lucienne; Vanden Bempt, Isabelle; Vermeer, Sascha; Woei-A-Jin, FJ Sherida H; Schöffski, Patrick; Weynand, Birgit; Sciot, Raf; Declercq, Sabine; Ceulemans, Laurens J.; Godinas, Laurent; et al. (Frontiers in Immunology, 2022)
A 35-year-old woman underwent bilateral lung transplantation for primary ciliary dyskinesia and developed vascular tumors over a slow time course. Initial presentation of non-specific vascular tumors in the lungs and liver for up to six years after transplantation evolved toward bilateral ovarian angiosarcoma. Tumor analysis by haplotyping and human leukocyte antigen typing showed mixed donor chimerism, proving donor origin of the tumoral lesions. In retrospect, the donor became brain dead following neurosurgical complications for a previously biopsy-proven cerebral hemangioma, which is believed to have been a precursor lesion of the vascular malignancy in the recipient. Donor-transmitted tumors should always be suspected in solid organ transplant recipients in case of uncommon disease course or histology; and proper tissue-based diagnosis using sensitive techniques should be pursued.